2015
DOI: 10.1021/acs.jafc.5b01883
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamaldehyde in a Novel Intravenous Submicrometer Emulsion: Pharmacokinetics, Tissue Distribution, Antitumor Efficacy, and Toxicity

Abstract: The purpose of our research is to find a new lipid emulsion to deliver a low water-soluble compound, cinnamaldehyde (CA). Its characteristics, pharmacokinetics, antitumor efficacy, and toxicity were evaluated. The mean particle size, zeta potential, and encapsulation efficiency of the submicromemter emulsion of CA (SME-CA) were 130 ± 5.92 nm, -25.7 ± 6.00 mV, and 99.5 ± 0.25%, respectively. The area under the curve from 0 h to termination time (AUC(0-t)) of SME-CA showed a significantly higher value than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…Our previous studies have shown that the interaction between chitosan and cinnamaldehyde (CA) can occur at an oil–water interface and can be controlled by changing the reaction pH and aldehyde/amino group ratio. , CA (3-phenyl-2-propenal) is the primary component extracted from the cinnamon plant (Cortex Cinnamomi) . It is a hydrophobic aromatic aldehyde that has been approved by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) for use as a food-flavoring agent .…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our previous studies have shown that the interaction between chitosan and cinnamaldehyde (CA) can occur at an oil–water interface and can be controlled by changing the reaction pH and aldehyde/amino group ratio. , CA (3-phenyl-2-propenal) is the primary component extracted from the cinnamon plant (Cortex Cinnamomi) . It is a hydrophobic aromatic aldehyde that has been approved by the Joint FAO/WHO Expert Committee on Food Additives (JECFA) for use as a food-flavoring agent .…”
Section: Introductionsupporting
confidence: 84%
“…21,22 CA (3phenyl-2-propenal) is the primary component extracted from the cinnamon plant (Cortex Cinnamomi). 23 It is a hydrophobic aromatic aldehyde that has been approved by the Joint FAO/ WHO Expert Committee on Food Additives (JECFA) for use as a food-flavoring agent. 24 It was reported that CA has no safety concerns based on the current levels of intake as a food additive.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The aldehyde part of CA that is mainly responsible for its pharmacological activity is easily to be oxidized when it was exposed in the blood [37][38][39]. When CA was administered (A and B) Renca cells were exposed to 20 mM MG132 for 1 h followed by the addition of CA as indicated.…”
Section: Discussionmentioning
confidence: 99%
“…*** p < 0.001, compared to the control. intraperitoneally to rats, CA was initially oxidized to cinnamic acid and then further metabolized mainly to hippuric acid, which could finally be recovered from urine [37,38]. Because cells were grown in the media containing fetal bovine serum in culture system, we could assume that CA is partly oxidized in the in vitro experimental system such as cell culture we used.…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamaldehyde (Figure a), a primary constituent of cinnamon bark oil, is an essential oil classified as GRAS (Generally Recognized As Safe) by the U.S. Food and Drug Administration (21 CFR 182.60). Cinnamaldehyde is known to have high antibacterial, antifungal, anti-inflammatory, and antioxidant activity; therefore, it is widely used in the food, drug, and cosmetic industries. For instance, cinnamaldehyde-containing films, particles, and NFs have shown the advantages of use of cinnamaldehyde in various applications including pharmaceutics, food, and antimicrobial packaging. For example, Qin et al showed that active packaging including cinnamaldehyde can lead to an increase in shelf life of fresh button mushrooms . In another study, it was shown that submicrometer emulsion of cinnamaldehyde can be used in clinical applications because of antitumor activity and pharmacokinetic properties .…”
Section: Introductionmentioning
confidence: 99%